Design and 3D printing of reconfigurable structures with pre-determined switching sequence - Shaikh Mohamed Akbar Mohamed Kaiash (Nanyang Technological University, 2020)
Reconfigurable structures are used in a wide range of fields such as space exploration, aerospace industries, biomedical, solar panels. This is due to its ability to transform into various shape and sizes depending on the design structure and material used. Reconfigurable structures can come in the form of mechanical pins and joints or by using shape memory polymers which adapts to its ambient. Reconfigurable structures are most commonly produced through three-dimensional (3D) printing. A bistable structure is a type of reconfigurable structure that can transform quickly from one functional shape to the other upon mechanical actuation. Potential applications can be found in mechanical/electromechanical devices from bio-inspired robots to deployable aero craft wings. An example of a bistable structure is a slap bracelet. Simple products as such prove to be convenient and easy to handle. On the larger scale, an aircraft wing that has bistability might assist in combating turbulence, doing so will improve the efficiency of flight. The aim of this project is to design a structure which is capable of two or more stable positions. Since these structures are 3D printed, we will be utilizing Fused deposition material (FDM) technology due to its low cost and simplicity. Basically, FDM Technology constructs objects layer by layer from the very bottom up by heating and extruding thermoplastic filament. These filaments are lightweight materials with a wide range of physical properties, suitable for both prototyping purposes and some functional applications. Thermoplastic polyurethane (TPU) is the main material for this design experiment as we require a certain degree of flexibility.